Exposed Embolic Coils Observed in a 64-Year-Old Male With Head and Neck Cancer Following Transarterial Embolization for Carotid Blowout Syndrome - Jia-Zheng Huang; Wei-Chen Lu; Bo-Ching Lee (Case Reports in Oncological Medicine)
Conclusions: Computed tomography angiography is essential for assessing the condition of the remaining embolic coils. In cases with thrombosed parent arteries, a conservative approach, like the transection of exposed coils, can be employed as part of the management strategy.